Different patterns of amygdala priming differentially affect dentate gyrus plasticity and corticosterone, but not CA1 plasticity - Vouimba, Rose-Marie; Richter-Levin, Gal (Frontiers in Neural Circuits, 2013)
Stress-induced activation of the amygdala is involved in the modulation of memory processes in the hippocampus. However, stress effects on amygdala and memory remain complex. The activation of the basolateral amygdala (BLA) was found to modulate plasticity in other brain areas, including the hippocampus. We previously demonstrated a differential effect of BLA priming on LTP in the CA1 and the dentate gyrus (DG). While BLA priming suppressed long term potentiation (LTP) in CA1, it was found to enhance it in the DG. However, since the amygdala itself is amenable to experience-induced plasticity it is thus conceivable that when activity within the amygdala is modified this will have impact on the way the amygdala modulates activity and plasticity in other brain areas. In the current study we examined the effects of different patterns of BLA activation on the modulation of LTP in the DG and CA1, as well as on serum corticosterone (CORT). In CA1, BLA priming impaired LTP induction as was reported before. In contrast, in the DG, varying BLA stimulation intensity and frequency resulted in differential effects on LTP, ranging from no effect to strong impairment or enhancement. Varying BLA stimulation patterns resulted in also differential alterations in Serum CORT, leading to higher CORT levels being positively correlated with LTP magnitude in DG but not in CA1. The results support the notion of a differential role for the DG in aspects of memory, and add to this view the possibility that DG-associated aspects of memory will be enhanced under more emotional or stressful conditions. It is interesting to think of BLA patterns of activation and the differential levels of circulating CORT as two arms of the emotional and stress response that attempt to synchronize brain activity to best meet the challenge. It is foreseeable to think of abnormal such synchronization under extreme conditions, which would lead to the development of maladaptive behavior.